Occult Orbital Injury with Dagger Fragment with Resulting Pneumocephalus - Lucía Jáñez-García; Enrique Mencía-Gutiérrez; Esperanza Gutiérrez-Díaz; Luis F. Moreno-García-Rubio; Laura Zarratea-Herreros; Álvaro Bengoa-González; Silvia Pérez-Trigo (Case Reports in Ophthalmological Medicine)
Penetrating injuries of the cranium are relatively uncommon, only 0.4% of all head injuries. In patients with disturbed conscious level, an extensive examination should be performed in the emergency unit to rule out transorbital penetrating brain injury. A 25-year-old male was attacked with a dagger. He presented with ethylic intoxication and the physical examination demonstrated a small skin injury on the lateral canthus of the left eye with a large periocular hematoma which prevented eyelid opening. Cranial CT scan showed a metallic intraorbital foreign body consisting of a fragment of a dagger which perforated the eyeball, and penetrated through the superomedial wall of the orbit into the anterior cranial fossa. Reconstruction of the eyeball was performed and the fragment was removed. Orbital injuries with a knife in situ are very unusual. Early identification and removal of retained foreign bodies are essential.